A rhodamine based dual chemosensor: Colorimetric recognisation of Zn2+ and fluorimetric recognisation of Sn4+. (2022) - Chethana, K.R.; Sureshkumar, Kempahanumakkagari; Muralikrishna, Sreeramareddy; Ramakrishnappa, Thippeswamy
Abstract: The potential newly contrived, synthesized and attested rhodamine derivative for colorimetric detection of Zn 2+ and fluorimetric detection of Sn 4+ . The action of probe with these two metals results in commutation of optical property which has been ascertained to be sensitive, selective and hardly influenced by other metal ions. The Zn 2+ induced absorption changes whereas the Sn 4+ induced emission changes with the probe. This dual sensing effective probe can be used for detection of these two physiologically/environmentally important metal ions by dual mode detection i.e. Zn 2+ by UV–Vis spectroscopy and Sn 4+ by and fluorescence spectroscopy.